Wild Anopheles funestus Mosquito Genotypes Are Permissive for Infection with the Rodent Malaria Parasite, Plasmodium berghei - Xu, Jiannong (Public Library of Science, 2013)

(untitled)
BACKGROUND: Malaria parasites undergo complex developmental transitions within the mosquito vector. A commonly used laboratory model for studies of mosquito-malaria interaction is the rodent parasite, P. berghei. Anopheles funestus is a major malaria vector in sub-Saharan Africa but has received less attention than the sympatric species, Anopheles gambiae. The imminent completion of the A. funestus genome sequence will provide currently lacking molecular tools to describe malaria parasite interactions in this mosquito, but previous reports suggested that A. funestus is not permissive for P. berghei development. METHODS: An A. funestus population was generated in the laboratory by capturing female wild mosquitoes in Mali, allowing them to oviposit, and rearing the eggs to adults. These F1 progeny of wild mosquitoes were allowed to feed on mice infected with a fluorescent P. berghei strain. Fluorescence microscopy was used to track parasite development inside the mosquito, salivary gland sporozoites were tested for infectivity to mice, and parasite development in A. funestus was compared to A. gambiae. RESULTS: P. berghei oocysts were detectable on A. funestus midguts by 7 days post-infection. By 18–20 days post-infection, sporozoites had invaded the median and distal lateral lobes of the salivary glands, and hemocoel sporozoites were observed in the hemolymph. Mosquitoes were capable of infecting mice via bite, demonstrating that A. funestus supports the complete life cycle of P. berghei. In a random sample of wild mosquito genotypes, A. funestus prevalence of infection and the characteristics of parasite development were similar to that observed in A. gambiae-P. berghei infections. CONCLUSIONS: The data presented in this study establish an experimental laboratory model for Plasmodium infection of A. funestus, an important vector of human malaria. Studying A. funestus-Plasmodium interactions is now feasible in a laboratory setting. This information lays the groundwork for exploitation of the awaited genome sequence of A. funestus.